Penentu Pemilihan Takaful Dalam Kalangan Muslim Di Pulau Pinang - Rapiai, Khairul Faizi Mohd (2021)
The development of Islamic financial system, especially the takaful industry internationally, has been the cornerstone when Malaysia was the first Asian state to implement it in 1985. This positive growth indicator can be seen from the increasing number of assets in the takaful industry from 2010 to 2017. In 2010 the number of takaful assets was RM14.6 billion while, in 2017 it increased to RM1.837 billion. However, this situation is quite different when in terms of takaful market share shows a small rate of 14.66 per cent in 2017 compared to 40.34 per cent for insurance. This poses an issue as the Muslim population in Malaysia is the largest group. Should the market takaful celebration be supported by Muslims. This is also quite different when there are more takaful branches in Penang than the number of Muslim population. Do Muslim residents in Penang choose takaful based on religious, external and internal factors? Based on this situation, this study looks at the factors that influence the determinants of Muslim Muslim candidates. Thus, this study has three objectives. First, identify the level of Muslim Muslim candidates for takaful. Second, analyzing the factors that influence the determination of the choice of Muslim participants in Penang against takaful. Third, it summarizes all the factors that influence the determination of the choice of Muslim participants in Penang against takaful. Total of 461 complete questionnaires have been received from respondents comprising Muslim participants. The results of the study were analyzed descriptively to determine mean value, standard deviation and percentage. Besides that, person and regression correlation test were also used.